INVESTIGATION OF 5 MOL% YSZ ELECTROLYTE FOR SOFC - Duygulu, Nilufer Evcimen; Ekerim, Ahmet (JOHN WILEY & SONS, 2011)
To investigate the performance of electrolyte for intermediate temperature SOFC, commercially available 5 mol% YSZ powder was used. Average particle size was measured as 0.3 mu m by using TEM. The sintering attitude of the powder was studied on pellets with conventional ceramic processing methods by means of mixing, pressing (110 MPa) and sintering. Sintering temperatures were determined as 1200, 1300 and 1400 degrees C for 3 h. Density measurements were done by using Archimedes technique. Sintered samples were observed via SEM and AFM and the best sintering temperature was selected as 1400 degrees C. Electrical property of YSZ pellets were measured after coating with platinum paste onto surface of the samples sintered at 1400 degrees C to serve as electrode. After that, pellets were heated at 800 degrees C for 1 h. This process was repeated for the other side. The ionic conductivity was measured by impedance spectroscopy in air between 500-900 degrees C.
Keywords: OXIDE FUEL-CELLS; FABRICATION; MICROSTRUCTURE; COMPONENTS; FILMS; Materials Science